2017
DOI: 10.1016/j.fertnstert.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Longer time interval between semen processing and intrauterine insemination does not affect pregnancy outcome

Abstract: There is no negative effect on pregnancy rate when IUI of processed sperm is delayed until the next day. This approach allows additional flexibility for couples when the male partner is not available on the day of ovulation, and it allows for a spread of workload in the laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
(16 reference statements)
1
6
3
Order By: Relevance
“…These results are in accordance with Jansen et al [27] who documented that there is no negative effect on pregnancy rate when IUI of processed sperm is delayed until the next day. Moreover, Lee et al [28] reported that insemination at least 36 h after ovulation is associated with increased pregnancy rate compared to IUI performed ≤36 h following ovulation.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with Jansen et al [27] who documented that there is no negative effect on pregnancy rate when IUI of processed sperm is delayed until the next day. Moreover, Lee et al [28] reported that insemination at least 36 h after ovulation is associated with increased pregnancy rate compared to IUI performed ≤36 h following ovulation.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, differences in screening/exclusion criteria and a lack of standardized IUI techniques between studies would also bias their comparability. Indeed, differences in sperm quality and processing, number of IUI cycles, cycle timing, and differences in ovarian stimulation have all been shown to affect IUI outcomes . It is also important to note that the control group included couples with an independent condition, unexplained infertility, which may be associated with fertility‐reducing factors that may bias these findings; however, given that all patients undergoing COH‐IUI inevitably have some form of infertility, it remains the most appropriate comparison group as all known and reversible causes of infertility have been screened and excluded.…”
Section: Discussioncontrasting
confidence: 85%
“… 48 Therefore, differences in the location of glycocalyx residues during selection/capacitation could explain the lower capacity of spermatozoa to recognize and bind to the zona pellucida when incubated for a relatively short capacitation time (1 h). 16 51 We additionally identified strong lectin pattern correlations during 4 h capacitation, e.g ., P1 in AAA, P2 for ConA, P1 with PNA, and P4 for WGA. The role played by these sugar relocation patterns could be related to proper sperm function and adequate oocyte recognition.…”
Section: Discussionmentioning
confidence: 93%